Competitive Advocacy Opportunity: Zeroing in U.S. Antidumping Enforcement - William W. Nye (U.S. Department of Justice, Antitrust Division, Economic Analysis Group (EAG), 2008)
Almost all countries have antidumping laws which regulate their imports. The United States and other countries enforce these laws within the terms of the World Trade Organization ("WTO"). There is a difference between U.S. enforcement and the enforcement approach of other countries, however. The United Statesbut not other countries of which I am aware–now uses 'zeroing' in its determination of whether imports are dumped. The use of 'zeroing' will almost always increase the level of any antidumping duty, and will sometimes create a duty where none would have been imposed, had the methodology not been used.
Keywords: 330